MODEL MANAJEMEN EPIDEMIOLOGI HIPERTENSI BERBASIS KOMUNITAS PESISIR - Robby, Krish Naufal Anugrah; Ma’rufi, Isa (Jurnal Manajemen Kesehatan Indonesia, 2025)
Hypertension remains a major public health challenge globally, with coastal communities facing unique vulnerabilities due to limited health infrastructure, low health literacy, and socio-economic constraints. This study aims to develop a community-based epidemiological management model for hypertension in coastal areas by analyzing the structural relationships among sociodemographic factors, risk behaviors, hypertension history, and healthcare access. Using a cross-sectional design, data were collected from 128 coastal residents in Puger Subdistrict, Jember, Indonesia. The study applied Partial Least Squares–Structural Equation Modeling (PLS-SEM) to explore causal pathways. The findings reveal that gender and education significantly influence risk behaviors, which in turn affect blood pressure grades and hypertension management. Despite a high prevalence of uncontrolled blood pressure, awareness and health-seeking behavior remain low. The structural model highlights the importance of behaviorally focused interventions targeting high-risk groups, particularly males and individuals with low education levels. The study underscores the need for community-based strategies that integrate risk-based management, health education, and culturally sensitive follow-up systems. This model offers a practical and contextual approach to strengthening hypertension control in underserved coastal populations